Organoids as a personalized medicine tool for ultra-rare mutations in cystic fibrosis: The case of S955P and 1717-2A>G - Silva, Iris A L; Doušová, Tereza; Ramalho, Sofia; Centeio, Raquel; Clarke, Luka A; Railean, Violeta; Botelho, Hugo M; Holubová, Andrea; Valášková, Iveta; Yeh, Jiunn-Tyng; Hwang, Tzyh-Chang; Farinha, Carlos M; et al. (Biochimica et biophysica acta. Molecular basis of disease, 2020)
BACKGROUND: For most of the >2000 CFTR gene variants reported, neither the associated disease liability nor the underlying basic defect are known, and yet these are essential for disease prognosis and CFTR-based therapeutics. Here we aimed to characterize two ultra-rare mutations - 1717-2A > G (c.1585-2A > G) and S955P (p.Ser955Pro) - as case studies for personalized medicine. METHODS: Patient-derived rectal biopsies and intestinal organoids from two individuals with each of these mutations and F508del (p.Phe508del) in the other allele were used to assess CFTR function, response to modulators and RNA splicing pattern. In parallel, we used cellular models to further characterize S955P independently of F508del and to assess its response to CFTR modulators. RESULTS: Results in both rectal biopsies and intestinal organoids from both patients evidence residual CFTR function. Further characterization shows that 1717-2A > G leads to alternative splicing generating <1% normal CFTR mRNA and that S955P affects CFTR gating. Finally, studies in organoids predict that both patients are responders to VX-770 alone and even more to VX-770 combined with VX-809 or VX-661, although to different levels. CONCLUSION: This study demonstrates the high potential of personalized medicine through theranostics to extend the label of approved drugs to patients with rare mutations.
Keywords: alely; Alleles; Cystic Fibrosis Transmembrane Conductance Regulator; Indoles; fluorescenční protilátková technika; Theranostics; lidé; Benzodioxoles; Precision Medicine; Genotype; chinolony; Fluorescent Antibody Technique; western blotting; protein CFTR; Humans; Mutation; Quinolones; Electrophysiology; indoly; aminopyridiny; individualizovaná medicína; Cystic Fibrosis; Intestinal organoids; Aminopyridines; CFTR modulators; benzodioxoly; Precision medicine; Aminophenols; Rare mutations; genotyp; cystická fibróza; mutace; aminofenoly; Blotting, Western; elektrofyziologie